Pengaruh Intellectual Capital dan Hedging Terhadap Nilai Perusahaan dengan Profitabilitas Sebagai Variabel Intervening - Hasna, Amalia; Abdurrahman (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
In a modern economy full of knowledge and technological developments, intellectual capital is seen as a source of value creation and sustainable competitive advantage. This research aims to analyze the influence of human capital, capital employed, structural capital and hedging on the value of banking companies in Indonesia with profitability as an intervening variable. This research uses secondary data obtained from company financial reports for 2014- 2021. The analysis technique used is multiple linear regression, path analysis and Sobel test with the help of the Eviews 12 program. The research results show that human capital, capital employed, structural capital have a positive effect on profitability but have no effect on company value. Other results show that hedging has no effect on profitability and company value. Research also shows that profitability is able to mediate the relationship between capital employed and structural capital on company value. However, profitability is not able to mediate the relationship between human capital and hedging on company value. A limitation in this research is that some companies do not include the notional value of derivatives as a hedging measurement in their financial reports.